AN EMPIRICAL ANALYSIS OF THE LEADER-MEMBER EXCHANGE AND QUITTING INTENTION MEDIATED BY JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT: EVIDENCE FROM SELF-FINANCED PUBLIC UNIVERSITIES - Nguyen, Danh Nam (Trường Đại học Đà Lạt, 2024)
This study investigates the effect of leader-member exchange on quitting intention as mediated by job satisfaction and organizational commitment in Vietnamese self-financed public universities. A questionnaire survey based on theory was conducted to obtain data from lecturers at eight self-financed public universities. The data were analyzed with a structural equation model. The model analysis demonstrated a significant linkage between leader-member exchange and quitting intention as mediated by job satisfaction and organizational commitment. Job satisfaction was found to be a significant predictor of high organizational commitment. Thus, the structural equation model results help clarify the mixed findings in the literature on the relationship between leader-member exchange and quitting intention.